(untitled) (Applied Biological Research, 2015)
The study was aimed to understand the kinetics of organophosphorus detoxifying enzyme carboxylesterase (EC 3.1.1.1) and to know the its sensitivity in Caenorhabditis elegans, a moist soil dwelling nematode used as model system for studying xenobiotics. Enzymatic hydrolysis of ρ-nitrophenylacetate (PNPA) showed a Km value of 20.95 μM, Vmax of 4.62 nmol min-1 mg-1 protein and substrate saturation of 350 μM for carboxylesterase (CaE) in vitro kinetics on exposure to dichlorvos from elegans. The IC50 with dichlorvos, an organophosphorus compound, was 81.16 nm at excess of Km. LB plot showed the Km, Vmax and Vmax/Km values of inhibited CaE: 19.57 µM, 2.88 nmol min-1 mg-1 protein and 0.14 min-1 mg-1 protein, respectively, at IC50 concentration of dichlorvos. Inverse LB plot revealed the inhibition of CaE in C. elegans irreversible in presence of dichlorvos. Hence this may be used as invertebrate